PENGARUH PENGAWASAN DAN PENGEMBANGAN KARIR TERHADAP PRESTASI KERJA PEGAWAI BANK BJB SERANG (Fakultas Ekonomi dan Bisnis Universitas Faletehan, 2024)
The aim of this research is to determine the effect of supervision and career development on the work performance of Bank BJB Serang branch employees. The research method used is the descriptive and causality method, namely a method that attempts to collect, present and analyze data so that it can provide a fairly clear picture of the object being studied, and a method that aims to examine the relationship or influence that exists between two or more variables. The data collection technique uses a questionnaire with measurements using a Likert scale. Sample determination was based on simple random sampling. Data analysis uses instrument tests, classical assumption tests, and hypothesis tests. Based on the results of research and statistical calculations, it is known that the multiple linear regression equation Y = 7.424 + 0.318X1 + 0.533X2. The correlation coefficient (R) = 0.795, while the coefficient of determination (R2) = 0.632, which means that the ability of the independent variable to explain the dependent variable is 63%, the rest is influenced by other factors. The calculated F value is greater than the F table (42.934 > 3.18), so it can be stated that Ho is rejected and Ha is accepted, which means that there is a significant influence between Supervision and Career Development on Employee Work Performance at Bank BJB Serang Branch.